Unique Pattern of Component Gene Disruption in the NRF2 Inhibitor KEAP1/CUL3/RBX1 E3-Ubiquitin Ligase Complex in Serous Ovarian Cancer - Martinez, Victor D. (Hindawi Publishing Corporation, 2014)
The NFE2-related factor 2 (NRF2) pathway is critical to initiate responses to oxidative stress; however, constitutive activation occurs in different cancer types, including serous ovarian carcinomas (OVCA). The KEAP1/CUL3/RBX1 E3-ubiquitin ligase complex is a regulator of NRF2 levels. Hence, we investigated the DNA-level mechanisms affecting these genes in OVCA. DNA copy-number loss (CNL), promoter hypermethylation, mRNA expression, and sequence mutation for KEAP1, CUL3, and RBX1 were assessed in a cohort of 568 OVCA from The Cancer Genome Atlas. Almost 90% of cases exhibited loss-of-function alterations in any components of the NRF2 inhibitory complex. CNL is the most prominent mechanism of component disruption, with RBX1 being the most frequently disrupted component. These alterations were associated with reduced mRNA expression of complex components, and NRF2 target gene expression was positively enriched in 90% of samples harboring altered complex components. Disruption occurs through a unique DNA-level alteration pattern in OVCA. We conclude that a remarkably high frequency of DNA and mRNA alterations affects components of the KEAP1/CUL3/RBX1 complex, through a unique pattern of genetic mechanisms. Together, these results suggest a key role for the KEAP1/CUL3/RBX1 complex and NRF2 pathway deregulation in OVCA.